Evaluation of anti-hyperglycemic and anti-hyperlipidemic effects of Naravelia zeylanica in streptozotocin- induced diabetic rats - Rajakalanithi A; Sujatha S; Swasthika P (International Journal of Phytomedicine, 2016)
Naravelia zeylanica DC (Ranunculaceae), a woody climber, have been used from ancient times to treat various ailments like rheumatoid arthritis, skin diseases, wound and ulcer. The present study was designed to investigate the anti-hyperglycemic activity of methanolic extract of Naravelia zeylanica (NZYM) using experimental diabetic model. Diabetes was induced in wistar rats by a single dose of streptozotocin (55 mg/kg i.p.) (STZ) and treated with NZYM at doses of 100 and 200 mg/kg for 45 days. Glibenclamide (5 mg/kg b.w.) was used as standard drug. Blood glucose and body weight were monitored at regular intervals and the levels of serum insulin, lipid and the carbohydrate metabolic enzyme in the liver were measured at the end of the study. Oral administration of NZYM and glibenclamide significantly reduced the blood glucose level (p<0.05), with increased serum insulin and significant alteration in lipid profiles and liver carbohydrate enzymes (p<0.05) after 45 days. Furthermore, the biochemical parameters correlated with the histopathological changes in the pancreas of STZ-induced diabetic rats, which structurally proved the efficacy of NZYM. The findings suggest that NZYM possess anti-hyperglycemic activity and anti-hyperlipidemic properties and restored STZ-induced pancreatic damage in diabetic rats. NZYM might therefore have a beneficial effect in treatment of diabetes mediated through regulation of carbohydrate metabolic enzyme activities.